2016
DOI: 10.18632/oncotarget.8461
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-endothelial transition and cancer stem cells: two cornerstones of vasculogenic mimicry in malignant tumors

Abstract: Vasculogenic mimicry (VM) is a functional microcirculation pattern in malignant tumors accompanied by endothelium-dependent vessels and mosaic vessels. VM has been identified in more than 15 solid tumor types and is associated with poor differentiation, late clinical stage and poor prognosis. Classic anti-angiogenic agents do not target endothelium-dependent vessels and are not efficacious against tumors exhibiting VM. Further insight into the molecular signaling that triggers and promotes VM formation could i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
134
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(139 citation statements)
references
References 62 publications
5
134
0
Order By: Relevance
“…However, EMT also contributes toward VM formation by stimulating tumor cell plasticity and degrading the extracellular matrix (EXCM) to mimic endothelial cells and to form VM channels. 29,39 In this study, we verified that AuNPs inhibited the expression of c-Myc and regulated the progression of EMT. MMP-2 is involved in the breakdown of EXCM and plays an important role in angiogenesis within tumors, 40 and hypoxia can activate this progression to facilitate tumor angiogenesis, invasion and metastasis.…”
Section: Discussionsupporting
confidence: 60%
“…However, EMT also contributes toward VM formation by stimulating tumor cell plasticity and degrading the extracellular matrix (EXCM) to mimic endothelial cells and to form VM channels. 29,39 In this study, we verified that AuNPs inhibited the expression of c-Myc and regulated the progression of EMT. MMP-2 is involved in the breakdown of EXCM and plays an important role in angiogenesis within tumors, 40 and hypoxia can activate this progression to facilitate tumor angiogenesis, invasion and metastasis.…”
Section: Discussionsupporting
confidence: 60%
“…The transition into endothelial cells is similar to an epithelial-mesenchymal cell transition. EMT is a process by which epithelial cells lose their epithelial characteristics and gain mesenchymal characteristics, acquiring the ability to invade and metastasize [28,29]. During EMT, the expression of epithelial markers such as E-cadherin are downregulated and the expression of mesenchymal markers such as Vimentin is upregulated [22,30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that EMT is associated with CSCs in human cancers. 52 CSCs possess the ability to self-renew and differentiate. 53 Moreover, CSCs have been validated and isolated from many human cancers including prostate cancer.…”
Section: Discussionmentioning
confidence: 99%